Stan Napięcia w Krążku Wirującym Mimośrodowo - Szelągowski, F. (Engineering Transactions, 1958)
This paper is devoted to the derivation of equations determining the values of the stresses Rθ, Rr, and θθ at every point of a disc rotating with constant angular velocity w about an axis passing through a point O1 at the distance a from the axis of the disc.